A CRITICAL REVIEW OF THE SCHOOL BASED- CURRICULUM (SBC) IN ENGLISH TEACHIG IN INDONESIA - Lina Farsia (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
In Indonesia, English has been taught for many years ago to enable the students to be able to communicate in English effectively. Unfortunately, the results of English teaching and learning at senior high schools were far expectation. Therefore, as one of the efforts by the government is to keep changing curriculum hoping that it can provide better results. School Based Curriculum (SBC) has been implemented in Indonesia in the action of perfecting the competence-based curriculum. SBC gives a school a chance to develop teaching materials based on the school potentials, students’ needs and ability and the need of the society around the school. SBC also focus on the process orientation rather than product orientation. SBC also expects integration of the material to be authentic or based on the real-life situation so the students know how the language works in real life context with the purpose that students can learn English better. However, the efficiency of developing and implementing SBC in most schools are very low because the tasks those need to be dealt with are very complex and difficult and in the reality, the schools have encountered a number of challenges in the process such as lack of capabilities and skills of teachers, lack of resources and material and not there is no sufficient fund.